2009
DOI: 10.1086/605608
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Culture (Vero)–Derived H5N1 Whole‐Virus Vaccine Induces Cross‐Reactive Memory Responses

Abstract: Novel strategies are required to provide rapid vaccine coverage in the event of an influenza pandemic. A phase I/II dose finding/formulation study was performed with a whole-virus H5N1 clade 1 A/Vietnam vaccine (2-dose priming regimen) to evaluate safety and immunogenicity. Seventy-seven of 141 subjects in this study received a booster (12-17 months after priming) with a 7.5-microg dose of a clade 2.1 A/Indonesia vaccine. The prime-boost regimen resulted in antibody responses against clade 1, 2.1, 2.2, and 2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 11 publications
4
22
0
Order By: Relevance
“…Presently, cell culture-based inactivated influenza vaccines are in clinical trials or have been approved for use in some countries (1,7,8,13,19). This approach has considerable advantages over egg-based vaccines because (i) it can lead to more rapid and larger-scale vaccine production (10); (ii) it may avoid the potential for selecting variants adapted for chicken eggs, which alters virus antigenicity (18); (iii) selection of high-yield vaccine seed viruses is needed for egg-based production; and (iv) it does not contain allergic components of eggs (16).…”
mentioning
confidence: 99%
“…Presently, cell culture-based inactivated influenza vaccines are in clinical trials or have been approved for use in some countries (1,7,8,13,19). This approach has considerable advantages over egg-based vaccines because (i) it can lead to more rapid and larger-scale vaccine production (10); (ii) it may avoid the potential for selecting variants adapted for chicken eggs, which alters virus antigenicity (18); (iii) selection of high-yield vaccine seed viruses is needed for egg-based production; and (iv) it does not contain allergic components of eggs (16).…”
mentioning
confidence: 99%
“…4 [5][6][7][8][9][10][11][12][13][14][15] There are pre-clinical reasons to believe that improvements to the vaccine seed virus generation process could lead to clinical improvements in cell culture-based vaccines.…”
Section: Fully Mammalian Cell Culture-based Influenza Vaccinesmentioning
confidence: 99%
“…67,69,71,72 Seroprotective levels of antibodies were achieved in 10-100% of the individuals, generally mirroring the variation observed in seroconversion. [67][68][69][70][71][72] In general, SRP levels were observed in >70% of the subjects after 2 conventional doses, and the proportion of subjects rose to >90% of the adults and >70% of the elderly following another dose at 6, 12-15 or 24 months following a single or a double dose administered earlier. 70 GMRs ranging from 1.6 to 32.8 have been observed, again following a pattern similar to SRC and SRP.…”
Section: Introductionmentioning
confidence: 95%
“…66 Human clinical trials for Vero cell-derived A/H5N1 influenza vaccines showed that doses ranging from 3.75 to 45 mg of hemagglutinin (HA) protein equivalent were well tolerated, induced robust clade-and cross-clade-reactive antibodies in pediatric and adult populations, and that these responses could be boosted 6-24 months later. [67][68][69][70][71][72] Seroconversion rates ranged from 6% to 86%; the responses were typically higher with a higher dose or following boosting, but lower when adjuvanted with aluminum salts, in older individuals, and against viruses belonging to heterologous clades. Significantly, responses persisted for 12-24 months in a considerable proportion (26-86%) of the subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation